Agressões em uma escola de ensino fundamental: visão dos alunos, professores e funcionários. - Medeiros, Corintha Maria Barreto (2006)
This study analyses 10 to 12 year-old children, 4th grade students, teenagers between 13 and 15 and students belonging to the 7th grade fundamental teaching experiences related to the aggression and violence in school environment and their perceptions about these experiences. The research was conducted during the school period of 2004 in a fundamental teaching unit located in São José do Rio Preto - SP, aiming to investigate if the aggression among students may cause the will of not going to school, as well as if the aggressions which are responsible for lacking of discipline interfere on the teaching-learning process development. In the first chapter of this work we have written about the contemporary view related to the agressions in school. European and some Latin-American authors have given support as a theoretical referential in this chapter. After that, we have sent the Brazilian production, which has as a theoretical reference master and doctor ship thesis. On the second chapter we have written about the researchs, the work, methods, the context, the partakers, the place where the field research was conducted, the used instruments for collecting and analyzing data. In the third chapter, we have mentioned the research results. At last, on the fourth chapter, we have gathered the arguing and final considerations. The mentioned experience s analysis conducted by the research individuals have indicated that the aggression acts and violence in school environment have points in common and points that are different when dealing with children and teenagers which can be linked, among other, to the characterists belonging to the different stage. It s been observed in this study that there s a major involvement in physical aggressions from students who come from 4th grades and a major participation of students from 7th grades relating to psychological aggressions. The classroom is considered as a place where the aggression acts are most common among students. It has been observed in analyzing the teachers and staff points of view concerning to the school violence that teachers consider the familiar context the most responsible element in the aggressive behavior of the students; on the other side, the two employees notices aggressions taken on the courtyard by vain reasons and jokes badly conducted.